An Automated Imaging Method for Quantification of Changes to the Endomembrane System in Mammalian Spheroid Models - Margaritha Mysior; Jeremy Simpson (Bio-Protocol)
Three-dimensional cell models, such as spheroids, represent a more physiological arrangement in which cells can grow, allowing them to develop cell–cell interactions in all dimensions. The most common methods for growing spheroids are scaffold-based, typically using either extracellular matrix or hydrogels as a physical support for the cellular assembly. One key problem with this approach is that the spheroids that are produced can be highly variable in size and shape. The protocol presented here allows for the systematic production of uniform spheroids in a short time frame by utilising a micropatterned plate. We show that spheroids can be used to investigate fundamental research questions, such as how the endomembrane system is organised in cells. Our protocol can be used in a manual or automated manner, potentially allowing scaling up for screening applications. Furthermore, without the complication of removing the spheroids from the extracellular matrix or hydrogel, as would be required in scaffold-based systems, spheroids can easily be used in other downstream applications.